2007
DOI: 10.1007/s10865-007-9138-z
|View full text |Cite
|
Sign up to set email alerts
|

Pain catastrophizing, physiological indexes, and chronic pain severity: tests of mediation and moderation models

Abstract: Catastrophizing about pain is related to elevated pain severity and poor adjustment among chronic pain patients, but few physiological mechanisms by which pain catastrophizing maintains and exacerbates pain have been explored. We hypothesized that resting levels of lower paraspinal muscle tension and/or lower paraspinal and cardiovascular reactivity to emotional arousal may: (a) mediate links between pain catastrophizing and chronic pain intensity; (b) moderate these links such that only patients described by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 47 publications
4
26
0
Order By: Relevance
“…Research has identified several psychological, interpersonal (Cano, 2004), physiological (Wolff et al, 2008) and neuroanatomical mechanisms (Gracely et al, 2004) that link catastrophizing to pain outcomes with both clinical and theoretical implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has identified several psychological, interpersonal (Cano, 2004), physiological (Wolff et al, 2008) and neuroanatomical mechanisms (Gracely et al, 2004) that link catastrophizing to pain outcomes with both clinical and theoretical implications.…”
Section: Discussionmentioning
confidence: 99%
“…Since the relation between persistent pain and physical disability have become clear in literature, researchers have turned their attention to questions concerning the processes by which catastrophizing impacts on pain outcomes, identifying several psychological, interpersonal (Cano, 2004), physiological (Wolff et al, 2008) and neuroanatomical (Gracely et al, 2004) correlates of catastrophizing that might explain its impact on pain experience.…”
mentioning
confidence: 99%
“…cognitive/emotional) processes. For example, several studies have confirmed a positive relation between stress, anxiety and increased lumbar muscle activity in CLBP (Flor et al, 1985;Watson et al, 1997;Geisser et al, 2005;Burns, 2006;Burns et al, 2006;Quartana et al, 2007;Wolff et al, 2008). Influences of cognitive processes on trunk muscle activity are likely to be velocity independent and may explain why no different adaptations are found with higher velocities.…”
Section: Adaptation Of Lumbar and Abdominal Muscle Activity To Highermentioning
confidence: 99%
“…Others have hypothesized that these compensatory changes in activity will place an excessive demand on the superficial muscles (Sterling et al, 2001;Hammill et al, 2008), restrict optimal trunk movement and generate high loading of the spine (Hodges and Moseley, 2003). If negative cognitions or emotions like anxiety or stress also contribute to increased lumbar muscle activity (Flor et al, 1985;Watson et al, 1997;Geisser et al, 2005;Burns, 2006;Burns et al, 2006;Quartana et al, 2007;Wolff et al, 2008), this may plead for an underlying mechanism which is not beneficial, but part of a vicious cycle in ongoing pain.…”
Section: Adaptation Of Lumbar and Abdominal Muscle Activity To Highermentioning
confidence: 99%
“…Research in this area has identified psychological, interpersonal (Cano, 2004), physiological (Wolff et al, 2008), and neuroanatomical (Gracely et al, 2004) correlates of pain catastrophising that might explain how pain catastrophising impacts on pain experience. The identification of the mechanisms that link pain catastrophising to pain outcomes has both clinical and theoretical implications.…”
mentioning
confidence: 99%